2013
DOI: 10.1136/gutjnl-2012-303615
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure and pharmacology of conventional thiopurine therapy in pregnant patients with inflammatory bowel disease

Abstract: Pregnancy has a major effect on maternal thiopurine metabolism. In utero the unborn child is exposed to 6-TGN, but not to 6-MMP. Sixty per cent of the infants were born with anaemia, which raises the question whether infants should be tested for possible anaemia immediately after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 28 publications
6
116
0
2
Order By: Relevance
“…In this fetus, the normalization of the pancytopenia was concurrent with the improvement of the T-cell counts with gradual steady improvement postpartum, raising the question of potential stressors on the fetal bone marrow that were absent or minimized after delivery. In utero exposure to azathioprine has been associated with fetal anemia [11] but not to the degree as seen in this case, and not with the significant pancytopenia with T-cell abnormalities. The unaffected co-twin raises the question of whether there may have been a differential response to an external exposure which then recovered with removal of the exposure.…”
Section: Discussionmentioning
confidence: 71%
“…In this fetus, the normalization of the pancytopenia was concurrent with the improvement of the T-cell counts with gradual steady improvement postpartum, raising the question of potential stressors on the fetal bone marrow that were absent or minimized after delivery. In utero exposure to azathioprine has been associated with fetal anemia [11] but not to the degree as seen in this case, and not with the significant pancytopenia with T-cell abnormalities. The unaffected co-twin raises the question of whether there may have been a differential response to an external exposure which then recovered with removal of the exposure.…”
Section: Discussionmentioning
confidence: 71%
“…Another study from France describing 86 pregnant IBD patients, underlined the general notion that thiopurine use during pregnancy is not associated with congenital abnormalities [10]. More recently, a prospective study in 30 female IBD patients giving birth to 31 infants during steadystate thiopurine therapy confirmed the general opinion that AZA and MP could be prescribed safely to pregnant women with IBD [11].…”
mentioning
confidence: 57%
“…A recent pharmacological study in thiopurine using pregnant females with IBD confirmed that the unborn child is exposed in utero to the pharmacologically active thiopurine metabolites 6-thioguanine nucleotides (6-TGNs). More importantly, almost two out of three neonates was born with (mild) anemia and in two newborns a thrombocytopenia was detected directly after birth [11], however not leading to apparent clinical problems. Leukopenia and anemia may occur as adverse events during AZA or MP use in non-pregnant IBD patients [12], this may be largely explained by elevated 6-TGNs levels.…”
mentioning
confidence: 99%
“…There are good safety data for hydroxychloroquine, sulfalazine, mesalazine and azathioprine, none of which are associated with any increase in congenital malformation rates or pregnancy loss. Although azathioprine was, in one study, 21 associated with neonatal anaemia, this was a small uncontrolled study and the results were not significant after adjustment for gestational age. 22 A prospective study is currently underway to further evaluate this.…”
Section: Immunomodulators and Immunosuppressantsmentioning
confidence: 73%